Pengaruh Latihan Kelincahan Terhadap Keterampilan Menggiring Bola Dalam Permainan Sepak Bola Pada Siswa SMP Negeri 7 Tondano - Zulkifly A. S Mashanafi; Bacilius Sukadana; Serli Ompi (STIKES Columbia Asia Medan, 2024)
The problem in this study is: Is there an effect of agility training on dribbling skills in soccer games for students of SMP Negeri 7 Tondano. Research objective: to determine the effect of agility training on dribbling skills in soccer games for students of SMP Negeri 7 Tondano. Research hypothesis: there is an effect of agility training on dribbling skills in soccer games for students of SMP Negeri 7 Tondano. The method used in this research is experimental method with the treatment in the form of agility training which is given for eight weeks. The population was all 20 grade 9 students, then divided into two groups, 10 students in the experimental group and 10 students in the control group. Data collection instrument: Test dribbling (Dribling) in a soccer game. The research design used: Randomized control groups pre-test and post-test design. Hypothesis testing using statistical techniques with the t test. The results of the hypothesis analysis, obtained t observations of tob = 9.772. while from the critical value table t with a significant level α = 0.05; n1 + n2-2 obtained t table value of tab = 2.101. This fact shows that the value of tob = 9.772 > tab = 2.101, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.